The Development of Physics Guided Inquiry Learning Package To Facilitate The Science Process Skills of Senior High School - Jehadan, Hermesianus; Nur, Mohamad; Supardi, Z.A. Imam (Universitas Malikussaleh, 2020)
The study aims to produce a guided inquiry learning materials to which is valid, practical and effective to facilitate the scientific process skills of senior high school (SMA) students on optical geometry topic. This is a development research with Four-D Model, that is Define, Design, Develop and Disseminate. This development research will be tested to the Grade XI science students of SMAN 1 Welak during their even semester of 2019/2020 using one group of pre-test and post-test. The data collection methods uses validation, observation, test and filling out questionnaries. The result of the analysis shows that: the developed learning materials is very valid; the learning process is carried out very well; and the students become more active in the learning process. The outcomes of students’ science process skills are increased, showed by the N-gain score is 0.95 which is classified in the high category. It can be said that the developed learning materials is valid, practical and effective to facilitate scientific process skills of senior high school students.